Numerical Simulation of Pellet Furnace Firing Area Case Study: Golgohar Mining Industrial Complex in Sirjan - Mohammad Javad Mahmoodabadi; Mohsen Talebipour (مجله مدل سازی در مهندسی)
In this research, numerical simulation of the hot gas flow in the firing area of the pelletizing furnace in Golgohar mining-industrial complex is studied. In this regard, Open-Foam software as an objective-oriented program and based on a proper programming language is used. The considered area includes the outlet plane of the burners, the down comer pipes, the combustion chamber, the space of the furnace and the wind box, while the pellet bed is regarded as a porous media. The investigated flow is assumed as steady-state, compressible and turbulent that passes through the pellet bed having a uniform porosity percentage. In order to model the turbulent flow, an appropriate two-equations approach is employed. In addition, the walls of the furnace are assumed to be insulated, the gradients of the temperature and pressure on the walls are considered to be zero, and non-sliding condition is regarded for the boundary condition of the velocity. The simulation results illustrate that the hot gasses are diverted on the sidewalls, which could be considered as an important factor for corrosion and decreasing their life. .